Influence of long-term inundation and nutrient addition on denitrification in sandy wetland sediments from Poyang Lake, a large shallow subtropical lake in China. (December 2016) - Zhang, Lu; Yao, Xiaolong; Tang, Chenjie; Xu, Huixian; Jiang, Xingyu; Zhang, Yunlin
Abstract: Wetlands at aquatic/terrestrial transition zones may play an important role in nitrogen removal due to the denitrification during inundation events. In this study, air-dried sandy sediment cores from Poyang Lake's wetlands were continuously inundated in the laboratory to investigate the rate, efficiency, and pattern of denitrification at the sediment-water interface (SWI). Denitrification rates responded to inundation in three stages: an adaptive period, a rapid growth period, and a stable period. The average denitrification rates during these stages were 52.62 ± 11.33 μmol N2  m −2  h −1, 115.74 ± 58.40 μmol N2  m −2  h −1 and 187.74 ± 16.44 μmol N2  m −2  h −1, respectively. Multiple regression analysis showed that inundation duration was the most important factor controlling denitrification rates at the SWI rather than nitrate concentrations, which were also positively correlated with denitrification rates. Changes in water content, oxidation-reduction potential ( E h ), and pH in the surface sediments, which were consequences of inundation, significantly influenced the denitrification rate ( p  < 0.05). The N2 O/(N2 O + N2 ) flux ratio in denitrification production varied from 1.61% during the adaptive period to 0.03% in the stable period, suggesting that continuous inundation of sediments in aquatic-terrestrial transition zones of Poyang Lake could decrease the proportion of greenhouse gases (N2 O). Since inputs of bioavailable nitrogen and phosphorus to Poyang Lake have increased in recent decades, the influence of elevated nutrients on denitrification under continuous inundation were also evaluated by simulation experiments. The results showed that increased nitrate or phosphate loading stimulate denitrification rates in sandy sediments during the inundation process. The addition of nitrate plus phosphate showed a stronger influence on denitrification than single nutrient additions. This study facilitates understanding of the influence of continuous inundation and elevated nutrients on denitrification in sandy sediments in aquatic/terrestrial transition zones. Graphical abstract: Highlights: Denitrification rates showed different stages under continuous inundation. Long-term inundation increased the denitrification efficiency. Long-term inundation contributed less incomplete denitrification and emission of N2 O. Elevated nitrate and phosphate stimulate denitrification under inundation condition.